PQ4R & Vocabulary Acquisition towards Bilingual Fiction Storybook For EFL Elementary Students in Reading Comprehension - Lu'luul Maknunah; Moh. Hafidz (SELL (Scope of English Language Teaching, Linguistics, and Literature) Journal, 2023)
PQ4R is students’ reading time in the bilingual fiction storybook to make faster through prepared questions. This research used qualitative research design to describe the real context of students’ reading using bilingual fiction storybook. The instruments were checklist to find the implementation of PQ4R in reading comprehension, and some questions to know the students’ vocabulary mastery. Then, the data analyzed to draw a conclusion. As the result, bilingual fiction storybook can enhance students’ ability on reading comprehension especially on students’ vocabulary enrichments, and makes students think critically through the content inside, because it contains picture inside to make students imagine the contents and it has two languages to make students easily to comprehend the text.